Maritime Security Governance: A New Strategy Management To Avoid Piracy In The Gog And Its Legal Guarantee - broohm, debi (Advances in Social Sciences Research Journal, 2021)
In the late 21st century, the growth of sea ships widened the horizons for trade on a global level. However, despite slow and cumulatively significant developments in transportation technology, during the era of sail, high sea maritime instability or the threats of piracy remained a significant obstacle to trade over long distances. In addition, with limited solidarity among all essential players in the region, several Gulf of Guinea (GoG) states can diversify their national attention to handle the pandemic instead of combating illegal activities at sea. Therefore, this article talks about the different factors of maritime piracy in the GoG, Comparing the trend across the region's different states (Togo, Benin, Nigeria, Ghana), the current maritime insecurity mitigation strategies proposed, and their gaps. Besides, a discussion around a knowledge gap in terms of accurate cooperation via the various policies implemented by those institutions brings us to propose coevolution governance in the shadow of the hierarchy and to create a maritime protect area (MPA) in the GoG country who do not have it yet, especially in Togo, Ghana, and Nigeria, and surround MPA with sustainably managed fishing areas where local small-scale fishers enjoy exclusive rights. The result shows that regionally it can help Centralize and diffuse the best practices, develop greater synergy among public policies and institutions, and nationally create greater sustainability of conservation with the integration of socio-economic concern and harmonization of strategic planning, practices, and policies.